Flood Inundation Map of Kampung Baru Muafakat Using Satellite Data and GIS Based Analysis - Mohamed Yusof, Muhammad Abqori; Mohd Bukari, Saifullizan (Recent Trends in Civil Engineering and Built Environment, 2026)
This study uses Geographical Information System (GIS) and satellite data to study the frequently occurring issue of floods in Malaysia, focused on Kampung Baru Muafakat. This study is focused on generating flood extension level in Kampung Baru Muafakat. In this study the appropriate method was used in flood mapping using QGIS to extract contour lines from Digital Terrain Model (DTM) data using the raster extraction tool. The Fill & Sinks method (Wang & Liu) is applied to identify catchment areas, unsupervised land use classification using the Semi-Automatic Classification Plugin (SCP). Isohyet maps are generated using the Inverse Distance Weighted method (IDW) based on rainfall data from CHRS, compared and validated with telemetry station data using the Discrepancy Ratio method. This study using a Digital Elevation Model (DEM) based on Triangulated Irregular Network (TIN) for flood depth and area analysis, revealing depths ranging from 0.2 to 1.2 meters, covering 10 out of 64 hectares. The findings add to a complete understanding of flood-prone areas, which will benefit in the development of sustainable urban design and disaster management strategies for Kampung Baru Muafakat.